PENEGAKAN HUKUM TERHADAP KEKERASAN DALAM RUMAH TANGGA DI TINJAU DARI HUKUM ADAT - Fariaman Laia (Jurnal Profil Hukum, 2025)
Law enforcement is an effort to implement the law and prevent discrimination in society, in order to achieve legal certainty in tracing whether this law is working well or not. And how this law provides protection for victims of violence. This research uses normative legal research methods with a conceptual and statutory approach. The research results show that law enforcement against domestic violence in terms of customary law is still inadequate. Therefore, strict law enforcement is very necessary to provide protection to victims, provide preventive action against perpetrators, and carry out rehabilitation to stop the cycle of violence. Enforcement of this law has not had a deterrent effect on perpetrators while there is already a PKDRT law. If we look at it from customary law, it depends on customary law, which is more about providing education to victims of domestic violence and giving fines to perpetrators. The laws and regulations should be enforced in accordance with the crimes committed. According to customary law, it is adequate, from the fines to the punishments that apply in each custom.